Pengaruh Teknik Konseling Clien Centered Terhadap Pengendalian Diri Berkata Kasar Pada Siswa Kelas XI IPS di SMAN 1 Lingsar Tahun Pelajaran 2023/2024 - Yogi Setiawan; Aluh Hartati; M. Najamuddin (Jurnal Eduforia: Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
Speaking harshly in general is a bad thing because it can have a negative impact on children. The reasons why children say rude things are internal factors such as family, economics, the main triggers are parents who often scold their children, children who make too many demands on their parents. The child's desire to get attention from their parents or people around them, even if that attention takes the form of a reprimand when they say harsh words, children have the desire to rebel and fight against older people because they are too restricted and pressured. Children usually say harsh things in their environment to get recognition from friends. -her friend. Therefore, to reduce rude behavior, group counseling sessions were provided using the client centered technique. The aim of this research is to examine the influence of the Client Centered technique on controlling harsh words in class XI IPS students at SMA Negeri 1 Lingsar for the 2023/2024 academic year. This research design uses One Group-Pre-test and Post-test. The population in this study was class from the results of the t-test, it shows that the calculated t value is 30.809 based on a significance level of 5% with db (N-1) = 9 – 1 = 8. It turns out that the limit for rejecting the null hypothesis stated in the t table distribution table is 2.306. This shows that the calculated t value is greater than the t table value, (2.302>2.306) so this research is said to be significant.